Spirituality Beyond Religiosity: Understanding Perceptions of Academic Cheating in Indonesia and Malaysia - Jamaluddin, Samudera Fadlilla; Lufityanto, Galang; Purba, Fredrick Dermawan; Lesmana, Cokorda Bagus Jaya; Andrianto, Sonny; Ardi, Rahkman; Siswadi, Ahmad Gimmy Prathama; Ridfah, Ahmad; Kristanto, Andreas Agung; Hutapea, Bonar; Suryani, Luh Ketut; Wisayanti, Suci; Achmad, Rendy Alfiannoor; Zwagery, Rika Vira; Fernandez, Elaine Frances; Ismail, Rozmi; Ishak, Mai Sumiyati; Zhi, Alfred Chan Huan; Hashim, Intan Hashimah Mohd; Khan, Aqeel; Yusoff, Ahmad Mustaqim; Jaladin, Rafidah Aga Mohd; Chobthamkit, Phatthanakit (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Cumulating evidence suggests that high levels of spirituality can foster integrity. However, integrity violations remain prevalent, even among populations with strong religious beliefs. This study collected data from 2,800 students across 17 academic institutions in Indonesia and Malaysia to examine the relationship between their levels of spirituality and their perceptions of academic cheating. Although both countries have predominantly Muslim populations, they differ in how religious practices are implemented. The results revealed a significant correlation between spirituality and perceptions of cheating in both countries. However, one aspect of spirituality in Indonesia diverged from the broader concept, underscoring the complex and nuanced relationship between spirituality and religion. While these concepts often overlap, they also exhibit distinct differences. Such differences in spirituality and religiosity may help explain the paradox of integrity issues, including the prevalence of cheating within religious communities.